Predictors of the failure of non-invasive ventilation in children with acute respiratory distress: A prospective observational study - Agrawal, Ruma; A. V, Lalitha; S, Sumithra; Kare, Jahanvi; Raj, John Michael (Indian Journal of Child Health, 2019)
Objective: The objective of this study was to determine the predictors of non-invasive ventilation (NIV) failure in pediatric acute respiratory distress/failure. Materials and Methods: This prospective observational study was conducted in a tertiary care hospital pediatric intensive care unit (PICU) for a period of 18 months. Children 1 month–16 years presenting with acute respiratory distress/failure, who were started on NIV, were included in the study. Demographic data, pediatric risk of mortality (PRISM) III score, vitals, and blood gas variables were monitored at admission and regular intervals, and incidence of NIV failure, length of PICU stay, hospital stay, and mortality rate was observed. Results: A total of 108 from 264 children with respiratory distress (40%) received NIV and 20/108 (18.51%) required endotracheal intubation. NIV failure patients had higher PRISM III score (median [interquartile range] - 8 [6.5, 13.5] vs. 7 [4.5, 8], p=0.025), lower admission pH (7.30 [0.066] vs. 7.34 [0.69], p=0.021), and higher number of children had associated comorbid illness (11/20 [55%] vs. 16/88 [18.18%], p=0.001) compared to NIV success group. On multivariate regression analysis, comorbid illness remains the significant independent predictor of NIV failure ([odds ratio 4.24; 95% confidence interval 1.322–13.576] p=0.015). Conclusion: Higher PRISM III score and comorbid illness were found as predictors of NIV failure.